Heavy maternal alcohol consumption and cerebral palsy in the offspring - O'Leary, Colleen marie; Watson, L.; D'antoine, Heather; Stanley, F.; Bower, C. (Wiley-Blackwell Publishing Ltd., 2012)
AIM The aim of this study was to investigate the association between heavy maternal alcoholconsumption and pre- peri- and postneonatally acquired cerebral palsy (CP).METHOD The records of all mothers with an International Classification of Diseases, revision 9 or10 (ICD-9 / -10) alcohol-related diagnostic code, indicating heavy alcohol consumption, recordedon population-based health, mental health, and drug and alcohol data sets from 1983 to 2007, andtheir children were identified through the Western Australian Data-linkage System. This ‘exposed’cohort was frequencymatched with mothers without an alcohol-related diagnosis and theiroffspring (comparison group). Cases of CP were identified through linkage with the WesternAustralia CP Register. Analyses were undertaken usingmultivariate logistic regression.RESULTS There were 23 573 live births in the exposed group (58.6% non-Aboriginal; 41.4%Aboriginal) and 292 cases of CP. The odds of pre / perinatally acquired CP were elevated forchildren of non-Aboriginal mothers with an alcohol-related diagnosis recorded during pregnancy(adjusted odds ratio 3.32; 95% confidence interval [CI] 1.30–8.48) and for Aboriginal children whenan alcohol-related diagnosis was recorded up to 12months before themother’s pregnancy(adjusted odds ratio 2.49; 95% CI 0.99–6.25). Increased odds of postneonatally acquired CPfollowing any alcohol-related diagnosis were found for non-Aboriginal children (adjusted oddsratio 7.92; 95% CI 2.23–28.14).INTERPRETATION These results suggest that heavy maternal alcohol consumption is a directcause of pre / perinatally acquired CP, and an indirect cause of postneonatally acquired CP, innon-Aboriginal children. The lack of an association for Aboriginal children requires furtherinvestigation but may be due to under ascertainment of alcohol use disorders during pregnancyand other aetiological pathways.Maternal alcohol use disorders, indicating alcohol abuse, harmful use, or dependence,1 are biological, psychological, and environmental risk factors for the offspring.2 Children are at risk of being exposed to a number of interacting factors stemming from the environment and the family which increase the risk of developing adverse health and cognitive and psychosocial problems.Heavy maternal alcohol use occurring during pregnancy increases the risk of a range of fetal effects, many of which are included under the umbrella term fetal alcohol spectrum disorders.3 Cerebral palsy (CP) is among the possible diagnostic features of structural or neurological brain damagerelated to prenatal alcohol exposure.4,5 However, the evidence to support this association is not strong.6 A handful of studies have reported a prevalence of CP in children with fetal alcohol syndrome of between 2% and 10%, but these are based on small numbers7–10 and many studies lack scientificrigour.